2021
DOI: 10.1039/d0np00056f
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of fungal meroterpenoid cyclases

Abstract: Complex cyclization reactions of fungal meroterpenoid cyclases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 96 publications
1
63
2
Order By: Relevance
“…This incomplete terpene cyclization toward unnatural substrate has not been reported in the meroterpenoid TPC reaction. 8,9) AscF produces the monocyclic structure from its native (10′S)-epoxyfarnesyl substrate, but the way of quenching a cation is different from those reported in this study. 13,14) It would be interesting to compare the substrate-binding manners of these reactions.…”
Section: Resultscontrasting
confidence: 77%
See 1 more Smart Citation
“…This incomplete terpene cyclization toward unnatural substrate has not been reported in the meroterpenoid TPC reaction. 8,9) AscF produces the monocyclic structure from its native (10′S)-epoxyfarnesyl substrate, but the way of quenching a cation is different from those reported in this study. 13,14) It would be interesting to compare the substrate-binding manners of these reactions.…”
Section: Resultscontrasting
confidence: 77%
“…TPC is thus a critical enzyme that constructs the basic molecular scaffolds of fungal meroterpenoids. 8,9) However, our knowledge of the substrate scope and reactivity of TPCs with unnatural substrates is rather limited. In this study, we tested a combinatorial biosynthesis by co-expressing the enzymes that produce the TPC substrate 1, with functionally distinct TPCs with different physiological substrates from 1, in Aspergillus oryzae NSAR1 as a heterologous expression host.…”
Section: Introductionmentioning
confidence: 99%
“…The A. oryzae / pyr1+2 was fed nicotinic acid and produced 4-hydroxy-6-(3-pyridinyl)-2H-pyran-2-one (HPPO), while A. oryzae / pyr4+5+6 was fed HPPO and produced deacetylpyripyropene E. The structures of these products suggested that the following biosynthetic reactions, Pyr1 and Pyr2, produce HPPO from nicotinic acid, CoA, and malonyl-CoA; Pyr6 transfers the farnesyl group at C-3 to yield 3-farnesyl-HPPO; Pyr5 epoxidizes the terminal olefin of the farnesyl group; and Pyr4 facilitates the cyclization of the epoxidated prenyl chain via protonation to produce deacetylpyripyropene E ( Figure 2 ). This was the first study that identified the function of the transmembrane meroterpenoid cyclase [ 16 ], and it paved the way toward investigations of the fungal meroterpenoid biosynthetic pathway. The A. oryzae / pyr1+2 strain was fed benzoic acid and generated 4-hydroxy-6-phenyl-2H-pyran-2-one (HpHpO), which was then fed to A. oryzae / pyr4+5+6 as a substrate to yield the un-natural meroterpenoid deacetyl-S14-95 ( Figure 3 ) [ 13 ], illustrating the ease of mutasynthesis with this heterologous expression system.…”
Section: Pyripyropene a Biosynthetic Pathwaymentioning
confidence: 99%
“…The ascofuranol was then oxidized by AscJ (NAD(P)-dependent dehydratase) to produce ascofuranone. AscI is a novel meroterpenoid cyclase sharing little similarity with known meroterpenoid cyclases, while AscF has similarity with Trt1 and known meroterpenoid cyclases [ 16 , 32 , 33 ]. The gene deletion of ascF resulted in the higher production of ascofuranone (501 mg/L) as compared with the wild-type strain (388 mg/L), illustrating the effectiveness of bioengineering to create a high-yield metabolite production system based on biosynthetic knowledge.…”
Section: Ascochlorin/ascofuranone Biosynthetic Pathwaysmentioning
confidence: 99%
“…Consequently, a wealth of novel skeletons, biosynthetic pathways, and bioactivities have provided new opportunities for drug discovery, genome mining, enzymology, and chemical synthesis. During the period covered in this review, there have been several more specialized reviews of fungal metabolites [ 26 , 27 , 28 ], including benzene carbaldehydes [ 29 ], trichothecenes [ 30 , 31 ], protoilludane sesquiterpenoids [ 32 ], meroterpenoids [ 33 , 34 , 35 ], meroterpenoid cyclases [ 36 ], terpenoids [ 37 ], and natural product biosynthetic genes and enzymes of fungi [ 17 , 18 , 38 , 39 ]. In addition, the isolation and chemistry of diterpenoids from terrestrial sources have been summarized [ 40 ].…”
Section: Introductionmentioning
confidence: 99%